The Effect of Non-Cash Payments System On People's Buying Interest: Case Study On Purchases At Malls In The Tangerang Area - Aspizain Caniago (Lead Journal of Economy and Administration, 2023)
Non-cash payments are currently an alternative payment method that is highly favored by some groups of people. The convenience and benefits obtained by using non-cash payments are the reason people make non-cash payments. This is often done in the buying and selling process at malls, including malls in the Tangerang area. The aim of the research is to find out how the influence of non-cash payments on the buying interest of people who are in the mall in the Tangerang area. The method used in this research is descriptive quantitative method. The data analysis technique used is a simple linear regression technique. The results of this study explain that there is a positive and significant effect of non-cash payments on people's buying interest of 87.9%.